Study of the effect of the compaction level on the hydrodynamic properties of loamy sand soil in an agricultural context - Mbarki, Yasmin; Gumiere, Silvio José; Celicourt, Paul; Brédy, Jhemson (Frontiers in Water, 2023)
Agricultural soil compaction adversely affects crop water use and yield performance and should be avoided or remediated through appropriate soil management strategies. The investigation of the impact of different levels of soil compaction on its hydrodynamic properties remains a crucial step in improving water use and crop yields. We examined five compaction levels of silty sand soil sampled from a potato field in the agricultural regions of northern Quebec (Canada). Soil hydraulic characteristics (saturated and unsaturated hydraulic conductivity, soil water retention capacity) were measured using the constant head method, the HYPROP device, and a WP4C dew point potentiometer. The sixteen hydraulic models integrated into the HYPROP software were fitted to the soil water retention curve (SWRC) data for the studied compaction levels. Statistical parameters such as the mean bias error, mean absolute error, correlation coefficient, and root mean square error were used to measure the performance of the models. The results show that saturated and unsaturated conductivity decreases with increasing soil compaction. The lowest saturated hydraulic conductivity (Ks) value is observed for the highest level of soil compaction, reflecting a solid medium with less pore space and connectivity. Among the hydraulic models, the Peters-Durner-Iden (PDI) variant of van Genuchten's unconstrained bimodal model (VGm-b-PDI) outperformed all other models for SWRC simulation of different soil compaction levels and was, accordingly, selected as the optimal model. This model was implemented in HYDRUS-1D to estimate the amount of irrigation for different compaction levels. We simulated irrigation scenarios with the dual-porosity model. The results indicated that soil compaction can strongly influence soil hydraulic properties and water differently. However, the amount of irrigation for the potato crop was optimal at a moderate level of soil compaction. Overall, combined HYPROP and HYDRUS 1D can provide helpful information on the soil hydraulics properties dynamics and a rigorous simulation for irrigation planning and management in potato fields.